The Belgrade Faculty of Fine Arts art collection - Erić Olivera (Nasleđe, 2016)
The paper discusses the significance of collections owned by educational/art institutions and their changing purpose and role through history. What makes university collections special is not only their role in the process of teaching/learning and research but also their role in the presentation of the achievements of the owning institution, which may considerably enhance its social prestige. Since the collection of an educational/art institution occupies a place at the interface between two worlds, those of universities and museums, it incorporates elements common to both, which contributes to its becoming an entity in its own right. The goal of the paper is to foster awareness of the importance of university collections both by the academic community and by the public interested in the phenomenon of collections existing at educational scientific/art institutions.